Algorithms to estimate the beginning of pregnancy in administrative databases1. (2nd May 2012) - Margulis, Andrea V.; Setoguchi, Soko; Mittleman, Murray A.; Glynn, Robert J.; Dormuth, Colin R.; Hernández‐Díaz, Sonia
ABSTRACT: Purpose: The role of administrative databases for research on drug safety during pregnancy can be limited by their inaccurate assessment of the timing of exposure, as the gestational age at birth is typically unavailable. Therefore, we sought to develop and validate algorithms to estimate the gestational age at birth using information available in these databases. Methods: Using a population‐based cohort of 286, 432 mother–child pairs in British Columbia (1998–2007), we validated an ICD‐9/10‐based preterm‐status indicator and developed algorithms to estimate the gestational age at birth on the basis of this indicator, maternal age, singleton/multiple status, and claims for routine prenatal care tests. We assessed the accuracy of the algorithm‐based estimates relative to the gold standard of the clinical gestational age at birth recorded in the delivery discharge record. Results: The preterm‐status indicator had specificity and sensitivity of 98% and 91%, respectively. Estimates from an algorithm that assigned 35 weeks of gestational age at birth to deliveries with the preterm‐status indicator and 39 weeks to those without them were within 2 weeks of the clinical gestational age at birth in 75% of preterm and 99% of term deliveries. Conclusions: Subtracting 35 weeks (245 days) from the date of birth in deliveries with codes for preterm birth and 39 weeks (273 days) in those without them provided the optimal estimate of the beginning of pregnancy among the algorithms studied. Copyright © 2012 John Wiley & Sons, Ltd.